Digital video and audio broadcasting technology : a practical engineering guide - Fischer, Walter (Signals and communication technology, 2010)
Deals with the most important digital television, sound radio and multimedia standards such as MPEG, DVB, DVD, DAB, ATSC, T-DMB, DMB-T, DRM and ISDB-T. This book contains chapters on the basics of technologies such as analog television, digital modulation, COFDM or mathematical transformations between time and frequency domains